Drug Therapy for the Elderly - Wehling, Martin; SpringerLink (Online service) (Vienna : Springer Vienna : Imprint: Springer, 2013)
With people aged 65 years and older currently making up the fastest growing age group throughout the world, the demographic revolution of an aging society will inevitably lead to increased pressure to develop a rationalistic and age-tailored process of diagnosis and treatment among the elderly. As aging people often suffer from several chronic diseases and are being treated with multiple medications concurrently, unwanted drug interactions occur more frequently. Whereas recent approaches have recommended to remove particular drugs from the medication regimen to avoid adverse effects, Drug Therapy for the Elderly underlines both indispensable and dispensable elements of drug treatment, providing the practitioner with: - Background information on the elderly population regarding their needs for particular drugs (with an eye to frailty, co-morbidity patterns, and special sensitivities regarding drug metabolism and excretion) - Practical advice about drug treatment surveillance parameters in the elderly - In-depth discussion of drugs in relation to the elderly with specific diagnoses - Integration of multimorbidity/polypharmacy situations into prioritization schemes - A plan for how to deal with the complexity of polypharmacy situations in a five-minute consultation An original classification of drugs is proposed by the editor which relates the power of effects, prognostic data, and tolerability to a prioritization scoring system. This approach is the first to not only provide a negative listing, but also integrates positive data into an overall assessment for drugs fit for the aged. Therefore, Drug Therapy for the Elderly serves as a timely reference for a wide array of physicians.
Foreword -- Part 1: General aspects -- Part 2: Special considerations with regard to organ systems based on geriatric clinical importance -- Part 3: Pharmacotherapy and geriatric syndromes -- Part 4: Further problem areas in gerontopharmacotherapy and pragmatic recommendations.
Keywords: Medicine; Toxicology; Geriatrics; Internal medicine; Medicine & Public Health; Geriatrics/Gerontology.; Internal Medicine; Pharmacology/Toxicology.